Estimation of Lithium-Ion Battery Health in Electric Bicycles Using Internal Resistance Measurement Method - Saputra, Riza Hadi; Dewanto, Muhammad Ridho; Maulana, Hadi (ELKHA : Jurnal Teknik Elektro, 2024)
This study evaluates the performance of a 36 Volt 10 Ah battery in an electric bicycle with a 350-Watt Brushless DC (BLDC) motor as an environmentally friendly alternative to overcome the negative impacts of motorized vehicle use in Indonesia. In addition, this study measured the State of Health battery"™s value of internal resistance, which is different from other studies that use capacity fading. With a focus on maximum travel distance and travel time, experiments were conducted without load and with a 70kg load. The no-load test was conducted only once, resulting in a travel time of 600 minutes and a distance of 330.1 Km. Although the battery was not discharged, the results were not in line with expectations, so the no-load test was only conducted once. In the 70kg load test, six trials were conducted with variable measurements of distance, battery voltage, and battery resistance. Results showed variations in distance between 50.7 km and 53.1 km, and travel time between 151 and 160 minutes. The battery voltage varied from 31.316 Volts to 31.850 Volts. The resistance in the battery also showed an increase of about 0.0001 ohms from 0.1132 ohms to 0.1139 ohms. Overall, the results from the study showed that as time and usage progressed, the battery voltage and internal resistance values tended to increase, while the distance and travel time tended to decrease. The internal resistance measurement method proved to be effective in assessing battery health as the State of Health value decreased throughout the experiment.